Postmodern Toplumda Ataerkil Düzen Değişiyor Mu? Popüler Kültür İçinde Cinsellik Kullanımına Eleştirel Bir Bakış: Biscolata Reklamları Ve Erkek İmgesi - Kahyaoğlu, İrem (The Turkish Online Journal of Design, Art and Communication, 2013)
The objective of this study is to examine the possible changing in patriarchal order and in today's consumer society how marketing tactics and ads use male or female body as a commodity with the aid of the image of man on Biscolata biscuit TV commercial. In this study, primarily the concept of sex, gender and image will be examined. After that, these ad serials (Biscolata biscuit) will be analyzed using the semiotic method of Roland Barthes.
Keywords: Gender; Cinsiyet; Sex; Cinsellik; Image of Man; Erkek İmajı; Semiology; Semiyoloji